Micro-Tom Tomato Response to Fertilization Rates and the Effect of Cultivation Systems on Fruit Yield and Quality - Naoki Terada; Kalara Dissanayake; Chiharu Okada; Atsushi Sanada; Kaihei Koshio (Horticulturae, 2023)
Fertilization is essential for the optimal growth and development of crops; however, the amount of fertilizer can cause positive or negative effects depending on its rate. In addition, the cultivation system plays a significant role in determining vegetative growth and fruit quality. Therefore, the objectives of this study were to examine the Micro-Tom response to different fertilization rates (first experiment), and to assess the effect of three different cultivation systems on its growth, yield, and fruit quality (second experiment). The fertilization rates used were (A) no fertilizer application control, (B) 0.026 g L−1, (C) 0.052 g L−1, (D) 0.13 g L−1, (E) 0.26 g L−1 standard, (F) 0.52 g L−1, and (G) 1.3 g L−1, and the cultivation systems were conventional, organic, and hydroponic. The results of the first experiment showed that plant growth and yield of Micro-Tom were highly influenced by the fertilization rate and Micro-Tom recorded the highest yield at 0.52 g L−1. In terms of the second experiment, the hydroponically grown Micro-Tom tended to accumulate amino acid, while organic and conventional systems showed more accumulation of sugars and organic acid; the highest yield was recorded in the hydroponic system. The yield obtained in the hydroponic systems was more than double that of the soil cultivation methods. The findings of this study can contribute to promoting the organic and hydroponic cultivation of tomatoes.